Perspectives of the General Public and Santri Guardians on the Rise of Immoral Cases in the Pesantren Environment - Hanif Syafrian Purnama; Hana Khoirun Nisa; Rinrin Sakinah; Agus Fakhruddin (Jurnal Al-Hikmah, 2023)
The rise of cases of immoral acts in the pesantren environment is a case that is commonly heard among the people of Indonesia. Pesantren, which should be a place of learning with the deepening of religion-based character education, is the opposite of being one of the places where immoral acts occur. This immoral act can be done by educators, workers and other students. Therefore, it is important to know the perspective of the community and the guardians of the students on the rise of this case, this needs to be considered because it affects the views, judgments and considerations for entering children into this religion-based educational institution. This research approach uses descriptive methods to obtain data by using questionnaires and also secondary data relating to the perspective of the general public and guardians of students. The results of this study are that the average respondent feels worried and sad about this incident, the average solution that is expected to prevent this case from happening is to provide sex education or religious education, carry out tighter supervision and improve communication with the pesantren as well as the students.